Pengaruh Kualitas Pelayanan, Produk Dan Harga Terhadap Minat Beli Pada Toko Online Shopee Di Kota Mamuju - Rusli; M.Tahir; Yati Heryati; Rhena J (Pustaka Digital Indonesia, 2023)
This study aims to determine the effect of service quality, product and price on buying interest in Shopee Online stores in Mamuju City. The sampling technique used in this study was purposive sampling technique. The research subjects used were individuals who had bought at the Shopee Online store, amounting to 90 respondents. The analytical tool used in this study is multiple linear regression analysis. To get the test results in this study, a classic assumption test is done, namely the normality test, the heterokedaticity test, and the multicorrelation test. Then hypothesis testing is performed. In this study the results of the Determination Test (R2) variable Service Quality, Products and Prices affect the purchase interest of 0.758 or by 75%, the rest is influenced by other variables by 25%. Simultaneously or together variable Service Quality, Products and Prices have a positive effect on the variable Purchase Interest. While partially (t test) the variable quality of service, product and price has a positive effect on buying interest in Shopee Online Store.